3, 3′-Diindolylmethane induces ferroptosis by BAP1–IP3R axis in BGC-823 gastric cancer cells. Issue 4 (21st February 2022) - Ye, Yang; Li, Xue; Feng, Guoquan; Ma, Ying; Ye, Fen; Shen, Haijun; Sun, Kang; Lu, Rongzhu; Miao, Shuhan
Abstract : To investigate the effect and potential mechanism of 3, 3′-diindolylmethane (DIM) on ferroptosis against gastric cancer, cells proliferation, lipid reactive oxygen species (ROS) and GSH level were measured in the BGC-823 gastric cancer cells after DIM treatment. Western blotting was used to detect the expression of SLC7A11, GPX4, IP3R and BAP1. Results showed that DIM could induce ferroptosis in the BGC-823 gastric cancer cells via upregulating lipid-ROS level and decreasing GSH generation. Besides, DIM also significantly reduced the protein level of SLC7A11 and GPX4, which was an important regulator of ferroptosis. In addition, DIM promoted the protein level of BAP1 and IP3R in a concentration-dependent manner in the BGC-823 gastric cancer cells. The knockdown of BAP1 could reduce IP3R level and DIM-induced ferroptosis of gastric cancer cells. Taken together, these results indicated that DIM could induce ferroptosis to exert anti-cancer effects via BAP1–IP3R axis, suggesting its effective therapeutic potential in gastric cancer.